Glycopyrrolate does not influence the visual or motor-induced increase in regional cerebral perfusion - Rokamp, Kim Z.; Olesen, Niels D.; Larsson, Henrik B.; Hansen, Adam E.; Seifert, Thomas; Nielsen, Henning B.; Secher, Niels H.; Rostrup, Egill (Frontiers in Physiology, 2014)
Acetylcholine may contribute to the increase in regional cerebral blood flow (rCBF) during cerebral activation since glycopyrrolate, a potent inhibitor of acetylcholine, abolishes the exercise-induced increase in middle cerebral artery mean flow velocity. We tested the hypothesis that cholinergic vasodilatation is important for the increase in rCBF during cerebral activation. The subjects were eleven young healthy males at an age of 24 ± 3 years (mean ± SD). We used arterial spin labelling and blood oxygen level dependent (BOLD) functional magnetic resonance imaging (fMRI) to evaluate rCBF with and without intravenous glycopyrrolate during a handgrip motor task and visual stimulation. Glycopyrrolate increased heart rate from 56 ± 9 to 114 ± 14 beats/min (mean±SD; p< 0.001), mean arterial pressure from 86 ± 8 to 92 ± 12 mmHg, and cardiac output from 5.6 ± 1.4 to 8.0 ± 1.7 l/min. Glycopyrrolate had, however, no effect on the arterial spin labelling or BOLD responses to the handgrip motor task or to visual stimulation. This study indicates that during a handgrip motor task and visual stimulation, the increase in regional cerebral blood flow is unaffected by blockade of acetylcholine receptors by glycopyrrolate. Further studies on the effect of glycopyrrolate on middle cerebral artery diameter are needed to evaluate the influence of glycopyrrolate on mean flow velocity during intense exercise.